Eighth Joint Multinational Judicial Colloquium - UNCITRAL (World Bank, Washington, DC, 2013)
The eighth joint UNCITRAL/INSOL/World Bank multinational judicial colloquium was held in Vancouver, Canada on 20-21 June 2009. Over 80 judges and government officials attended from some 40 states, representing a broad range of practical experience and perspectives, particularly with respect to cross-border insolvency, from diverse legal systems. The colloquium provided a widely-welcomed opportunity for judges to have contact with each other and to further their understanding of the various national approaches to cross-border insolvency cases. A number of judges attending had not attended previous colloquia.